The role of ubiquitous tools in horizontal and vertical learning - Mohammad Jaki, Mohd Syafiq; Ab Jalil, Habibah; Hassan, Aminuddin; Ismail, Ismi Arif; Abd Rahman, Fadzilah; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This paper discusses the role of ubiquitous tools in supporting and affecting horizontal and vertical learning styles in the higher education context. Horizontal learning and vertical learning are imperative, always come together and appear in the learning process. Horizontal learning refers to learning only on the surface while vertical learning requires deeper understanding of what is being learnt. Ubiquitous tools refer to devices that are portable and can be used with greater access, available anywhere and all the time. Typical examples are mobile phones (cellphones or hand phones), smart phones, handheld computers (Personal Digital Assistant or PDAs), laptop computers and other devices. This paper aims to clarify on how the use of ubiquitous tools can enhance learning styles. The advantages of ubiquitous tools can open up new opportunities to access information and knowledge, thus facilitating students' learning. The main issue discussed in this paper is to what extent ubiquitous tools can support horizontal and vertical learning in the university education context.